Optimizing Organic Waste Management Using Black Soldier Fly Larvae: A Financial Perspective - Widyarsana, I Made Wahyu; Ramadhini, Dehan Nabiilah; Muflihah, Lilih; Utami, Inayah Wiji; Yulianti, Yulianti (Brawijaya University, 2025)
The use of Black Soldiet Fly (BSF) in processing organic waste offers numerous benefits, including significant waste volume reduction, transformation of waste into value-added products such as organic fertilizers, livestock feed, and fish feed, as well as supporting the implementation of a circular economy. However, organic waste processing practices in BSF larvae or what is more widely known as maggot with maggot houses often face challenges, particularly in terms of funding. Financial factors are crucial elements that determine the operational sustainability of such waste management systems. This study aims to analyze the financial conditions and operational feasibility of Rumah Maggot Cimincrang and Imah Maggot Bantaran. The study employs the Net Present Value (NPV) method, which calculates the present value of total net revenues after deducting costs over a specific period. NPV serves as a tool to assess the financial feasibility of an activity. If the NPV is positive, the activity is considered financially feasible and profitable. The results indicate that the operational feasibility of Rumah Maggot Cimincrang can be achieved through product diversification, such as producing maggot meal and maggot oil, alongside optimizing marketing efforts via digital platforms like e-commerce with a NPV of IDR 161,769,698. Meanwhile, Imah Maggot Bantaran, which operates on a community-based model, is already financially viable with an NPV of IDR 4,333,190,208. However, further efforts are needed to enhance operational consistency, ensuring the production of sustainable products over the long term.